PENYELESAIAN SENGKETA BISNIS MELALUI ARBITRASE: PERBANDINGAN EFISIENSI EKSEKUSI PUTUSAN ARBITRASE DI INDONESIA DAN SINGAPURA: Business Dispute Resolution through Arbitration: A Comparative Study of the Enforcement Efficiency of Arbitral Awards in Indonesia and Singapore - Silaban, Kenjiro Adriano (Fakultas Hukum, Universitas Trisakti, 2025)
The purpose of this essay is to compare the effectiveness of Singapore's and Indonesia's enforcement of arbitral awards. The main problem is the procedural obstacles that both jurisdictions' arbitration-based dispute settlement processes face. This article answers the following legal questions: what factors affect the execution of arbitral award enforcement in Indonesia and Singapore, and why Indonesian parties typically choose the Singapore International Arbitration Centre (SIAC) over the Indonesian National Arbitration Board (BANI) for arbitral disputes. Using a normative legal method, this study supports the secondary legal framework with primary legal materials such the 1958 UNCITRAL Model Law, the Indonesian Arbitration and Alternative Dispute Resolution Act (AAPS), the BANI Arbitration Rules, and legal periodicals. According to the article's conclusion, Indonesian parties favor SIAC as an arbitration venue because of its more effective enforcement and procedural procedures. However, because arbitrators may not fully comprehend Indonesian law, this choice could result in misunderstanding. Furthermore, because there is less judicial interference, no necessity to record arbitral awards with the local court, and few grounds for annulment under Singaporean law, the implementation of arbitral awards in Singapore is more feasible than in Indonesia.